Nitrogen-doped carbon derived from horse manure biomass as a catalyst for the oxygen reduction reaction - Gasidit Panomsuwan; Chadapat Hussakan; Napat Kaewtrakulchai; Ratchatee Techapiesancharoenkij; Ai Serizawa; Takahiro Ishizaki; Apiluck Eiad-ua (My University, 2022)
This work shows the potential utilization of horse manure as a precursor for synthesizing nitrogen-doped carbons for electrocatalytic oxygen reduction reaction.
Keywords: Carbon fibers; Electrocatalysts for Energy Conversion